The Power of Positive Coaching The Mindset and Habits to Inspire Winning Results and Relationships. - Colan, Lee J. (Lee Joseph); Davis-Colan, Julie (McGraw Hill-Ascent Audio, 2019)
To unleash the power of positive coaching, excellent leaders start with themselves - their own mindset, performance, assumptions, awareness, relationships, and learning. The Power of Positive Coaching addresses these aspects of self-leadership with compelling research, examples, and simple tools.